MENINGOCOCCEMIA IN CHILDREN-AN UNDER RECOGNIZED PUBLIC HEALTH PROBLEM IN PAKISTAN - Bibi, Saima; Gilani, Syed Yasir Hussain; Siddiqui, Tahir Saeed; Anis ur Rehman; Syed, Subhanullah; Muhammad, Khyal (Journal of Ayub Medical College Abbottabad, 2022)
Background: Meningococcemia is a serious bacterial disease caused by Neisseria meningitidis resulting in septicemia and meningitis in previously well individuals and is associated with serious consequences including mortality. As the data from our region is scarce, the study was conducted with an aim to highlight the disease manifestations and outcomes so that appropriate interventions are devised. Methods: A descritive study was conducted in Pediatrics A Unit from 1st March 2020 to 30th September 2021 after approval of institutional review board. Children admitted with features of meningococcemia in the form of fever and typical petechial purpuric rash were included in the study. Results: A total of 46 patients with meningococcemia were included in the study. Of these, 24 (52.2%) were male. Majority of the patients 22(47.8%) were in the age group of 1 year to five years, Major complications were meningitis in 39 (84.8%), septic shock in 26(56.5%) and purpura fulminans in 12(26.1%) patients. Mortalit[y was documented in 6(13%) patients. Outcome was associated with age. (p= 0.039). There was a significant difference in outcome in patients with prolonged PT/APTT (p=0.031), purpura fulminans (p= 0.000) and septic shock (p= 0.021). Conclusion: Meningococcemia is prevalent in our region in pediatric population. The disease has a fulminant course with a myriad of complications and potentially fatal outcomes especially in children under one year of age.